Analisis Faktor Risiko Kejadian Stunting Pada Anak Umur 0 Sampai 12 Bulan Di Wilayah Kerja Puskesmas Kuta Baro Kabupaten Aceh Besar - Nandita, Aisya Shaka; Fadhil, Iziddin; Amna, Eka Yunita (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2024)
Stunting is a growth and development disorder in children who experience poor nutritional intake, malnutrition, repeated infections and inadequate psychosocial stimulation, so for the diagnosis and management of stunting a comprehensive examination is needed. And stunting can also be defined as length or height less than - 2 standard deviations (SD) below the WHO median length and height curve (<-2 SD). Indonesia's 2022 Toddler Nutrition Status regarding stunting decreased from 24.4% in 2021 to 21.6 in 2022. The incidence of stunting in toddlers is high, namely Aceh Province (31.2%). This study aims to determine the dominant risk factors affecting the incidence of stunting in children aged 0-12 in the Kuta Baro Health Center working area, Aceh Besar Regency. To determine the risk factors for stunting in children aged 0-12 in the working area of the Kuta Baro Health Center, Aceh Besar Regency. This type of research uses obsevational analytic with the research design used is Cross Sectional. This research was conducted from March to July 2024. The results showed that the logistic regression analysis showed that the variables of exclusive breastfeeding and hand washing sanitation had a multivariate dominant relationship to stunting, with an exclusive breastfeeding p-value <0.05, namely 0.004 and hand washing sanitation p-value <0.05, namely 0.024. The dominant factors that have the most influence on the incidence of stunting are exclusive breastfeeding and hand washing sanitation. So that socialization / counseling to raise mothers' awareness of the importance of exclusive breastfeeding to infants / toddlers and promotion of PHBS in the working area of Puskesmas Kuta Baro Aceh Besar Regency.